HUBUNGAN POLA MAKAN PENYAKIT INFEKSI DAN STATUS MEROKOK KELUARGA DENGAN KEJADIAN STATUS GIZI BALITA - Sari, Erma Puspita; Yunola, Satra (JOURNAL OF MIDWIFERY SCIENCE, 2021)
Background : Nutrition is one of the determinants of the quality of qualified, healthy, intelligent and productive human resources. Objective: To find out the relationship between eating patterns, infectious diseases, and family smoking status with the incidence of nutritional status of children under five. Objective: To find out the relationship between eating patterns, infectious diseases, and family smoking status with the incidence of nutritional status of children under five. Methods: This research is a quantitative analytic study with a cross sectional approach. Data collection in this study used secondary and primary data, by using questionnaires and interviews. While secondary data is data obtained from the patient's status in the medical record section. Results: The results of the analysis obtained the Odds Ratio (OR) obtained a value of 12,358 which means that the respondents under five whose eating patterns are quite have a chance. The results of the analysis also obtained an OR value of 5.721, which means that respondents under five who experience infectious diseases have a chance. And the results of the analysis also obtained an OR value of 7.235, which means that respondents under five whose families smoke will have a chance.Conclusion: There is a relationship between eating patterns of infectious diseases and family smoking status with the nutritional status of children under five. Keywords: Diet, infectious disease, family smoking status and nutritional status of children under five